Molecular detection of Paracoccidioides brasiliensis in road-killed wild animals - Richini-Pereira, Virginia Bodelao [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Griese, Juliana [UNESP]; Theodoro, Raquel Cordeiro [UNESP]; Macoris, Severino Assis da Graca [UNESP]; Da Silva, Reinaldo Jose [UNESP]; Barrozo, Ligia; Tavares, Patricia Morais E. Silva; Zancope-Oliveira, Rosely Maria; Bagagli, Eduardo [UNESP] (Taylor & Francis Ltd, 2008)
Paracoccidioides brasiliensis infections have been little studied in wild and/or domestic animals, which may represent an important indicator of the presence of the pathogen in nature. Road-killed wild animals have been used for surveillance of vectors of zoonotic pathogens and may offer new opportunities for eco-epidemiological studies of paracoccidiodomycosis (PCM). The presence of P. brasiliensis infection was evaluated by Nested-PCR in tissue samples collected from 19 road-killed animals; 3 Cavia aperea (guinea pig), 5 Cerdocyon thous (crab-eating-fox), 1 Dasypus novemcinctus (nine-banded armadillo), 1 Dasypus septemcinctus (seven-banded armadillo), 2 Didelphis albiventris (white-eared opossum), 1 Eira barbara (tayra), 2 Gallictis vittata (grison), 2 Procyon cancrivorus (raccoon) and 2 Sphiggurus spinosus (porcupine). Specific P. brasiliensis amplicons were detected in (a) several organs of the two armadillos and one guinea pig, (b) the lung and liver of the porcupine, and (c) the lungs of raccoons and grisons. P. brasiliensis infection in wild animals from endemic areas might be more common than initially postulated. Molecular techniques can be used for detecting new hosts and mapping 'hot spot' areas of PCM.
Keywords: Paracoccidioides brasiliensis; Paracoccidiodomycosis; road-killed; animals; molecular epidemiology